Modes of reperfusion in clinical liver transplantation - Post, Stefan; Bleyl, Jörg-Uwe; Golling, Markus T.; Herfarth, Christian; Otto, Gerd (Langenbecks Archiv für Chirurgie, 1995)
A retrospective analysis of 60 orthotopic liver transplantations was performed to elucidate the effect of three types of rinse solutions (Ringer's solution, modified Carolina rinse, and autologous blood) and two types of revascularization (simultaneous vs sequential portal and arterial reperfusion) on various parameters of early postoperative graft function. The only statistically significant association revealed by multivariate analysis was a positive correlation between donor age and SGOT/SGPT peak levels postoperatively. In this limited sample no beneficial properties of Carolina rinse and/or simultaneous arterialization were verified. Despite modifications of reperfusion, there were 2 cases of primary nonfunctioning graft. However, these cases were associated with elderly donors, prolonged cold storage and, in 1 case, marked steatosis. Large-scale prospective trials are required to verify or disprove experimental data on the use of varying modes of reperfusion.
Elektronische Reproduktion der Druck-Ausgabe 27. April 2016
Gesehen am 26.08.2025